COVID 19 and Increased Security Challenges in Northern Nigeria: Interrogating Armed Banditry in Northwestern Nigeria - Noah Echa Attah; Usman Sambo; Babayo Sule; Muhammad A. Bello; M. Yoserizal Saragih (Budapest International Research and Critics University, 2021)
The COVID 19 pandemic has become a global health issue that now intersects with security issues, especially in African countries. The outbreak of the virus in Africa has halted political, economic and social activities, including countering armed violence. Nigeria is one of the African countries that is faced with security challenges, ranging from Boko Haram insurgency, rural banditry, farmers-herders clash, kidnapping, robbery to piracy among others. However, much attention has concentrated on mitigating the spread of COVID 19 pandemic and the provisions of palliatives to cushion the effects of the abrupt stoppage of formal and informal economic activities. This study examines the intersections between the pandemic and armed banditry in Northwestern. It appears that armed bandits have intensified attacks on communities, against the background of government’s anti-COVID policy. Government has equally re-strategized in responding to the bandits’ attacks. The study gathered data from documented sources and media reports and were analyzed, using content analysis. The study observed that the armed bandits used the COVID 19 lock down policy to increase attacks on some communities, thereby providing a complex dimension to rural banditry in Northwestern Nigeria. This led to increased air and land offensive by the Nigerian military against the bandits. This study recommends among others that government should increase surveillance and adopt strict measures on movements to curtail the activities of the bandits.